Land fragmentation, climate change adaptation, and food security in the Gamo Highlands of Ethiopia. (22nd October 2018) - Cholo, Tesfaye C.; Fleskens, Luuk; Sietz, Diana; Peerlings, Jack
Abstract: Household food security among smallholder farmers is sensitive to a variable and changing climate, requiring farmers in the Gamo Highlands of Ethiopia to adopt new land management practices to improve food security. Agricultural land in the Gamo Highlands is highly fragmented. The extent to which land fragmentation (LF) moderates the food security effects of sustainable land management (SLM) practices is unknown. This study used probit and Poisson models to explain this relationship. The study found that food insecurity was severe during the food shortfall season. LF provides more potential opportunities for improving food security than challenges. Furthermore, SLM practices had both positive and negative effects on food security and their effects were conditioned by the magnitude of LF. Reducing severe LF through the assembly of small parcels into larger heterogeneous plot clusters could enhance food security by exploiting synergies between adaptation practices and LF.